A Retrospective Analysis of Efficacy and Toxicity of Bevacizumab in Combination with Chemotherapy for the Management of NSCLC in Bangladeshi Population - Hoque, Md Ehteshamul; Hassan, Md Rashidul; Karim, Mrs Shanaz; Siddque, Ashraful Alom; Siddiqui, Md Mahmudur Rahman (Anwer Khan Modern Medical College Journal, 2017)
Background: From the perspective of Bangladesh, it has been scrutinized that patients with advanced NSCLC diseases are being treated with conventional chemotherapy which is too main stream. In addition to this general practice, reports of several clinical trials of targeted therapy i.e. use of Bevacizumab dramatically showed the longest overall survival (OS) in patients. Methods: This is a cross sectional descriptive type of observational study to analyse the responses both positive and negative of metastatic NSCLCA patients treated with Bevacizumab in combination with preferable chemotherapy regimen admitted in Anwer Khan Modern Hospital in Dhaka Bangladesh. The record of the responses of patients from January 2009 to December 2015 was assessed. Results: A total of 35 patients were observed in this study. Patients received 6 cycles of Bevacizumab in combination with platinum based chemotherapy for every three weeks as an induction therapy. Maintenance therapy was given to patients at intervals for a certain period of time. A total of 35 patients were in the assessment who were intermittently checked on a consistent interlude for a median follow up on the basis of response criteria. It was astonishing that each of the patients underwent good tolerance as well as response of Bevacizumab except of 3 which is very sporadic. Despite the enhancement in efficacy and safety consequences with platinum-based chemotherapy, this typical cytotoxic approach has reached a therapeutic plateau, with the prognosis for this clinical condition remaining deplorable. Conclusion: So addition of Bevacizumab as a targeted therapy option along with traditional chemotherapy regimen provides excellent upshot to Bangladeshi Patients diagnosed with metastases NSCLC. These represent the first evidence of improvement in treatment outcomes of chemotherapy with targeted therapies in the first-line treatment of advanced NSCLC. Anwer Khan Modern Medical College Journal Vol. 8, No. 1: Jan 2017, P 10-16